Impacts of Olive Mill Wastewater on Soil Environment in the Mediterranean Region - Kreba, Sleem Ali (Journal of natural sciences, life and applied sciences, 2022)
Olive Mill Wastewater (OMW) is a potential issue for olive oil producers in the Mediterranean region, where it is known as the main producers worldwide. OMW has serious impacts on the environment and agriculture and has double nature; it is a strong pollutant and at the same time a possible source of valuable components. OMW can improve soil properties and productivity if it is added with the right amount and at the right time. This review article considers studying the effects of OMW on soil biological, chemical, and physical properties and processes. It summarizes the importance of olive oil and the common extraction methods besides OMW’s properties. It also offers essential information about OMW’s impacts on crops and its treatment methods. This article was prepared to help people with different specialties and interests such as farmers, food producers, researchers and scientists in environmental and agricultural sectors. There is still need for improvement of effective OMW treatment methods to reduce its environmental impacts and to be reused in irrigation. It is recommended that OMW should be developed to produce biochar which can be used to improve soil properties and fertility, and new resistant plant breeds to phenolic toxicity should be developed.